Nyúltvelői neurovascularis kompresszió A szekunder hypertonia ritka oka - Nádas Judit (ORVOSI HETILAP, 2014)
Compression of the rostral ventrolateral medulla oblongata is one of the rarely identified causes of refractory hypertension. In patients with severe, intractable hypertension caused by neurovascular compression, neurosurgical decompression should be considered. The authors present the history of a 20-year-old man with severe hypertension. After excluding other possible causes of secondary hypertension, the underlying cause of his high blood pressure was identified by the demonstration of neurovascular compression shown by magnetic resonance angiography and an increased sympathetic activity (sinus tachycardia) during the high blood pressure episodes. Due to frequent episodes of hypertensive crises, surgical decompression was recommended, which was performed with the placement of an isograft between the brainstem and the left vertebral artery. In the first six months after the operation, the patient's blood pressure could be kept in the normal range with significantly reduced doses of antihypertensive medication. Repeat magnetic resonance angiography confirmed the cessation of brainstem compression. After six months periodically increased blood pressure returned, but in smaller extent and less frequent. Based on the result of magnetic resonance angiography performed 22 months after surgery, re-operation was considerd. According to previous literature data long-term success can only be achieved in one third of patients after surgical decompression. In the majority of patients surgery results in a significant decrease of blood pressure, an increased efficiency of antihypertensive therapy as well as a decrease in the frequency of highly increased blood pressure episodes. Thus, a significant improvement of the patient's quality of life can be achieved. The case of this patient is an example of the latter scenario. Orv. Hetil., 2014, 155(21), 838-842.